A Service Oriented Approach for Synchronous Collaborative RIAs Development - Gaspar, Tiago C.; Teixeira, Cesar A. C.; Prado, Antonio F. do (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2010)
The concepts and technologies that de ne Web 2.0 have revolutionized and extended computer assisted collaborations. Collaborative applications with synchronous multimedia communication, rich interfaces and using the Web as a platform are examples of such revolution. Experiences in that domain allow the identification of commonalities among these applications. A service oriented architecture might be a good choice to lower coupling between platforms and increase software reuse. Based on practical experience, this paper presents a software reuse approach. Web Services and GUI components are proposed to aid development of synchronous multimedia collaborative RIAs in a systematic manner.